2021
DOI: 10.3389/fnins.2021.638973
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep Quality in Nurses Working or Having Worked Night Shifts: A Cross-Sectional Study

Abstract: Night shifts are part of clinical care. It is unclear whether poor sleep quality of nurses working both consecutive night shifts and day shifts after quitting night shifts is common. In this cross-sectional study, Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality as study outcome. Univariable and multivariable linear and logistic regressions were performed to compare PSQI score and prevalence of poor sleep quality between 512 nurses currently working consecutive night shifts and 174 nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
2
13
1
1
Order By: Relevance
“…The current study found that nurses at a university hospital had a high prevalence of poor sleep quality (75.9%). The rate was somewhat higher than reported in a previous report from China (62.1%) [ 24 ] The current study may have a higher poor sleep quality rate because there were several shiftwork patterns, particularly rotational shiftwork (452 persons: 72.7%), as previously reported [ 22 ]. Rotational shiftwork is reported to affect the circadian rhythm, with an odds ratio of 1.456–2.348 times for poor sleep quality [ 23 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Discussioncontrasting
confidence: 41%
“…The current study found that nurses at a university hospital had a high prevalence of poor sleep quality (75.9%). The rate was somewhat higher than reported in a previous report from China (62.1%) [ 24 ] The current study may have a higher poor sleep quality rate because there were several shiftwork patterns, particularly rotational shiftwork (452 persons: 72.7%), as previously reported [ 22 ]. Rotational shiftwork is reported to affect the circadian rhythm, with an odds ratio of 1.456–2.348 times for poor sleep quality [ 23 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Discussioncontrasting
confidence: 41%
“…Another study reported that of 207 participants 34.30% were found with poor sleep quality (total PSQI score > 10) [ 23 ]. Also, in another study, more than 50% of nurses reported poor sleep quality [ 24 ]. In our study, midwives' sleep disturbance was similar to the findings of previous studies, which was reported to be 30–50%.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, a study showed that working years >15 years (P = 0.04) was associated with poor sleep quality [ 23 ]. Huang et al believe that as work experience increases due to increased night shifts, sleep quality decreases slightly, which may be due to adaptation to night shifts and work-family conflict [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nursing interns are a special subgroup of the nursing team and have received tremendous attention from multidisciplinary researchers ( Mei et al, 2022c ). Nursing interns experience transition-related stressors as well as non-habitual sleep–wake schedule ( Zhang et al, 2019 ), which leads to night-shift intolerance and poor sleep quality among them ( Huang et al, 2021 ). Previous studies reported that approximately 22.8–38.2% of nursing interns experience sleeping problems ( Lai et al, 2020 ; Gao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that approximately 22.8–38.2% of nursing interns experience sleeping problems ( Lai et al, 2020 ; Gao et al, 2021 ). Additionally, circadian rhythm disruption affects the levels of ghrelin, leptin, insulin, cortisol, and melatonin among night-shift workers, causing poor sleep quality ( Ulhôa et al, 2015 ; Huang et al, 2021 ). Poor sleep adversely affects their physical and mental health (e.g., cardiovascular risk, mood disorders, etc.)…”
Section: Introductionmentioning
confidence: 99%